2001
DOI: 10.2460/ajvr.2001.62.1212
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a transforming gene (E5) of bovine papillomavirus in sarcoids obtained from horses

Abstract: This study documented that activation and expression of the E5 gene is evident in sarcoids obtained from horses. These data support the conclusion that infection with bovine papillomavirus is important in the initiation or progression of sarcoids in horses. Treatment strategies designed to increase immune recognition of virally infected cells are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
61
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 41 publications
1
61
0
Order By: Relevance
“…In more recent years, PCRbased detection methods offering greater sensitivity have been used to demonstrate the presence of BPV DNA in sarcoids. The reported detection rate varies between study groups, from 73 (Bloch et al, 1994) to 88-91 (Martens et al, 2001a, b) and 96-100 % (Carr et al, 2001a, b;Otten et al, 1993). This variation may be attributable to differences in tumour collection methodology, as the lowest rates of detection are seen in studies using tumours stored in formaldehyde for long periods of time.…”
Section: Bpv As the Causative Agent Of Sarcoidsmentioning
confidence: 88%
See 2 more Smart Citations
“…In more recent years, PCRbased detection methods offering greater sensitivity have been used to demonstrate the presence of BPV DNA in sarcoids. The reported detection rate varies between study groups, from 73 (Bloch et al, 1994) to 88-91 (Martens et al, 2001a, b) and 96-100 % (Carr et al, 2001a, b;Otten et al, 1993). This variation may be attributable to differences in tumour collection methodology, as the lowest rates of detection are seen in studies using tumours stored in formaldehyde for long periods of time.…”
Section: Bpv As the Causative Agent Of Sarcoidsmentioning
confidence: 88%
“…Both BPV types 1 and 2 have been detected in sarcoid tumours with the predominant types varying between studies. BPV DNA has not been detected in samples obtained from horses without sarcoids or in non-sarcoid equine tumours or equine papillomas (Otten et al, 1993;Nasir et al, 1997;Carr et al, 2001a, b). However, it has been found in some cases of dermatitis and the significance of this is as yet unknown (Angelos et al, 1991;unpublished observations).…”
Section: Bpv As the Causative Agent Of Sarcoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…26,29,34 In subsequent work, Southern blots were used to identify BPV1 or BPV2 genome(s) within tumor tissue, 1,2,19,38 and polymerase chain reaction (PCR)-based surveys routinely demonstrate that up to 100% of sarcoids contain BPV DNA. [12][13][14]23,24,27,38,39 A limited number of studies have been designed to investigate the role of BPV in cellular transformation in equine tissue. These studies have identified early and late gene transcripts in at least a subset of naturally occurring sarcoids indicating the initiation of viral transcription and replication.…”
mentioning
confidence: 99%
“…20 In these cases, virion production is considered limited to infected cells within the overlying epithelium. 4,[10][11][12]47 Papillomaviruses are most notable for causing cutaneous papillomas or warts with hyperplasia of the statum spinosum and/or neoplasia of the cutaneous stratified epithelium. 26,32 The viruses are also capable of causing lesions in the alimentary tract and within oral mucosa in the case of bovine (Bos taurus) papillomavirus 4 4 and canine (Canis familiaris) oral papillomavirus, 9 respectively.…”
mentioning
confidence: 99%